1997
DOI: 10.1088/0034-4885/60/12/002
|View full text |Cite
|
Sign up to set email alerts
|

The realization of atomic resolution with the electron microscope

Abstract: The high-resolution electron microscope has evolved into a sophisticated instrument that is capable of routinely providing quantitative structural information on the atomic scale. Applications of atomic-resolution imaging can now be found in many scientific fields, and its impact on the knowledge and understanding of atomistic processes has been profound. Better control over instrumental parameters, enhanced reliability of signal recording, and novel methods for imaging and data processing are areas of highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(38 citation statements)
references
References 376 publications
(418 reference statements)
0
38
0
Order By: Relevance
“…General overviews of the application of electron microscopic methods to QC are given by Hiraga (2002) and Beeli (2000), and in general by Smith (1997), for instance.…”
Section: Electron Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…General overviews of the application of electron microscopic methods to QC are given by Hiraga (2002) and Beeli (2000), and in general by Smith (1997), for instance.…”
Section: Electron Microscopymentioning
confidence: 99%
“…Radiolytic effects predominantely occur at low energies, knock-on effects only at high-energies. The induced defects accelerate atomic diffusion considerably (Gittus, 1978;Smith, 1997). This may overcome the sluggish kinetics of low-temperature phase transformations.…”
Section: Hrtem (High-resolution Transmission Electron Microscopy)mentioning
confidence: 99%
“…In the very same year, it was also demonstrated that two diffracted beams could be passed simultaneously through the microscope objective lens to form interference fringes, or lattice fringes, the first representative image of a crystal lattice. Over the years the resolution gradually improved and the contrast mechanisms became well understood, for reviews of these developments, see Smith (1997Smith ( , 2008. Correlating the image to atomic positions is not always simple since the relative phases of the diffracted beams depend on the thickness and microscope focus and aberrations, so the imaging of dislocation core structures relied on extensive image simulations, at least until the recent introduction of aberration correctors (Kisielowski et al 2006).…”
Section: Direct Imaging Of Dislocation Core Structuresmentioning
confidence: 99%
“…The spatial resolution of transmission electron microscopy (TEM) has steadily improved over the years, and observations at atomic level have been made for many types of material and different structural defects. 4 The purpose of this article is to provide a brief overview of some recent atomic-level electron microscopy studies that illustrate epitaxial growth of II-VI compound semiconductors on several common substrates. Opportunities for closer examination of these materials with the latest generation of aberration-corrected electron microscopes (ACEMs) are also discussed.…”
Section: Introductionmentioning
confidence: 99%